Being Assessed: The Struggles and development of Language Teachers Identity of a Minority EFL Pre-service Teacher during A Teaching Practicum - Jeremy Steven Christian; Moh Hasbullah Isnaini (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
The current research investigated the tensions and struggles of a minority, an anxious Chinese Indonesian, English Foreign Language (EFL) pre-service teacher (PST) during the teaching practicum within his teacher education program. Employing an autoethnographic design, the researcher served as both the subject who shared the live experiences and the researcher who tells the story. As it is an autoethnographic study, the main data of this research is reflective narratives which comprised one thousand words, talking about his own lived experiences. The narratives focused on the teaching practicum activities recounting the experiences of teaching two vocational high school classes and the emotions or tensions accompanied it. The narrative was examined through a six-phase reflexive thematic analysis. Four themes were generated: anticipatory anxiety managed through intensive preparation; the evaluative gaze as the central trigger of anxiety, revealed by the contrast between graded teaching and unobserved substitute teaching; a critical incident of assessment failure intensified by social comparison with peers; and an emergent but unfinished teacher identity marked by tension between idealism and responsiveness. The findings indicated that the practicum advanced the writer’s teacher identity less through smooth success than through emotionally charged rupture and reflection. The study offers a situated, first-person account that may inform how teacher-education programs support anxious and minoritised pre-service teachers.